Induction of labor using prostaglandin vaginal gel: cost analysis comparing early amniotomy with repeat prostaglandin gel. (April 2016) - Beckmann, Michael; Merollini, Katharina; Kumar, Sailesh; Flenady, Vicki
Abstract: Background: In a randomized controlled trial of two policies for induction of labor (IOL) using Prostaglandin E2 (PGE2) vaginal gel, women who had an earlier amniotomy experienced a shorter IOL-to-birth time. Objective: To report the cost analysis of this trial and determine if there are differences in healthcare costs when an early amniotomy is performed as opposed to giving more PGE2 vaginal gel, for women undergoing IOL at term. Study design: Following an evening dose of PGE2 vaginal gel, 245 women with live singleton pregnancies, ≥37+0 weeks, were randomized into an amniotomy or repeat-PGE2 group. Healthcare costs were a secondary outcome measure, sourced from hospital finance systems and included staff costs, equipment and consumables, pharmacy, pathology, hotel services and business overheads. A decision analytic model, specifically a Markov chain, was developed to further investigate costs, and a Monte Carlo simulation was performed to confirm the robustness of these findings. Mean and median costs and cost differences between the two groups are reported, from the hospital perspective. Results: The healthcare costs associated with IOL were available for all 245 trial participants. A 1000-patient cohort simulation demonstrated that performing an early amniotomy was associated with a cost-saving of AUD289 (AUD7094 vs AUD7338) per woman induced, compared with administering more PGE2. Propagating the uncertainty through the model 10, 000 times, early amniotomy was associated with a median cost savings of AUD487 (IQR −AUD573, +AUD1498). Conclusions: After an initial dose of PGE2 vaginal gel, a policy of administering more PGE2 when the Modified Bishop's score is <7 was associated with increased healthcare costs compared with a policy of performing an amniotomy, if technically possible. Length of stay was the main driver of healthcare costs.